Relevansi Pemahaman yang Benar Tentang Gereja Bagi Orang Percaya Masa Kini - Sabda Budiman; Yabes Doma (Sekolah Tinggi Teologi Bethel Ambon, 2021)
This wrong understanding of the church affects one's actions towards applying one's faith. The importance of proper and basic knowledge of the church is the need of every believer today—the need for a renewal of the correct understanding of the church. The need for a fundamental and biblical account of the church encourages the author to deepen the discussion of the church's doctrine. The problem in this research is: what are the misconceptions about the church? And what is the correct understanding of the church according to the Bible and its relevance for believers today? This study aims to discuss the knowledge of the church based on the perspective of the Bible and its significance for believers today. The method that the author uses is a qualitative-descriptive research method. The results of this study reveal that the church is not a building, denomination, or